Implementasi Observasi Profiling Peserta Didik sebagai Persiapan Perencanaan Pembelajaran di Kelas IB SDN Gayamsari 02 Semarang - Nurhayati, Novi; Siswanto, Joko; Nyoman, Ngurah; Isnuryantono, Effensi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The aims of this study were (1) to map the learning styles of students in the learning design in class IB at SDN Gayamsari 02 Semarang (2) to design a learning design that is in accordance with the results of profiling observations of students in class IB at SD Negeri Gayamsari 02 Semarang. The research method used is descriptive qualitative. The population in this study were all grade 1 students at SD Negeri Gayamsari 02 Semarang, while the research sample was Class IB at SD Negeri Gayamsari 02 Semarang with a total of 26 students. There were 13 female students and 13 male students. The stages of this research are planning, implementation, and reflection. The observation results show that the designed learning has not been able to facilitate the diversity of the characteristics of students in the class. Preparation of the learning design begins with observing student profiling, followed by mapping learning styles, planning methods, models and approaches to be used in accordance with all student learning modalities. Learning design by making mapping. The use of the Teaching at The Right Level (TaRL) approach, the Problem Based Learning (PBL) learning model, and the Timeboard media in class IB SD Ngeri Gayamsari 02 Semarang. Reflection activities aim to identify and evaluate inappropriate learning designs. Keywords: Profiling, Learning Styles, Characteristics